Peningkatan Kualitas dan Nilai Tambah Biji Kopi melalui Pelatihan Pengelolaan Coffee Drying House (CDH) dan Strategi Pemasaran Digital di Kelurahan Lubuk Buntak - Syahri, Riduan; Nasrullah, Abdi; Rahmayati, Desy (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity aimed to improve the quality and added value of coffee beans produced by farmers in Lubuk Buntak Village through the optimization of Coffee Drying House (CDH) management and the implementation of digital marketing strategies. The methods used were intensive training on good CDH management practices and the provision of materials on digital marketing strategies such as branding, social media marketing, and e-commerce. The results obtained from this activity were an increase in farmers' knowledge of the correct coffee drying process, an improvement in the quality of coffee beans, and an increased interest of farmers in marketing their coffee products digitally.